Pengaruh Penggunaan Kontrasepsi Depo Provera terhadap Angka Kejadian Hipertensi di Puskesmas Ngoresan Surakarta - Viola Belivia Tripuspita; Yulia Lanti Retno Dewi; Sigit Setyawan (Nexus Kedokteran Komunitas, 2013)
Background: One of health problem which often suffered by Depo Provera contraception acceptor is hypertension. Ngoresan Public health Center is one of Health center in Surakarta which has many Depo Provera user as acceptor of Family Planning. Looking at mortality number because of hypertension in Indonesia is quite high and the complication which emerged as much as well, so that writer is interested to do research about contraception user of Depo Provera influence towards hypertension emergence at Ngoresan Surakarta Public Health Center. Methods: The research was used observation analytical methods with Cohort Retrospective study approach which conducted on March-April 2013. The research has done to 60 women, age 20-40. Sample was taken using fixed exposure sampling technique. The data was analyzed with Chi Square (x2) test. Results: The result shows that there was significant impact for contraception use of Depo Provera towards hypertension case number in Ngoresan Surakarta Public Health Center. Based on calculation which done with chi square test with significance level 5%, calculation using SPSS 20, obtained that p=0.009 < significant value limit p= 0.05 Conclusions: Depo Provera contraception increased hypertension case number of acceptor Family Planning between aged 20-40 year women in Ngoresan Surakarta Public Health Center. Keywords: Depo Provera contraception, hypertension